REALIZATION OF EXTRADITION BASED ON UNITED NATIONS CONVENTION AGAINST TRANSNATIONAL ORGANIZED CRIME AND THE ROLE OF IMMIGRATION IN IMPLEMENTATION - Dwi Nuryani (Journal of Law and Border Protection, 2022)
Extradition is a path taken by countries that want to return criminals to the locus delicti country. Extradition is carried out based on an extradition treaty bilaterally or multilaterally, if there is no agreement, extradition can be carried out on the basis of good relations and if the interests of the country so desire. There are several guiding principles in the implementation of extradition in Indonesia, which are contained in Law no. 1 of 1979 concerning extradition. In addition, Indonesia is also one of the countries that ratify UNCATOC which in article 16 regulates or discusses extradition. The Directorate General of Immigration is a government agency that has duties and functions in terms of traffic of people leaving or entering the territory of Indonesia, in the implementation of these duties and functions there are intersections or benefits in the implementation of extradition which can provide information on Indonesian citizens or foreigners in terms of traffic of people. entering and leaving the territory of Indonesia, providing assistance in the form of travel letters to suspected perpetrators of crimes, including them on the list of prevention and deterrence, coordinating with state representatives abroad or immigration attaches in the diplomatic process, and much more. There for immigration is an institution that has an important role in the implementation of extradition because it relates to other countries which are included in the duties, functions, and powers of immigration.